Elaboración de Material de Apoyo Mediante Fabricación Aditiva para la Asignatura de Organización y Métodos (2021)
3D printing with the advancement of technology, has delivered to the world, societies and companies, an important development of technology for the manufacture and creation of new elements. In this research, the design of three dismountable figures was carried out using additive manufacturing technology, in order to facilitate teachers to transmit knowledge to students and that in one way or another the student perceives complex information more easily and practice, thus seeking to make the chair of the subject of Organization and Methods more didactic by applying the concepts of methods of time taking and control of movements and obtain a better quality in the classrooms, for this it is necessary to rely on new technologies, which are tools that serve as a support or supplement in student learning where they can express or make known their creativity and innovation by developing their capacities and competencies. Keywords: AutoCAD, additive manufacturing, 3D technolo